Effect of moxibustion combined with cupping therapy in the treatment of lumbar disc herniation of Qi-stagnation and Blood-stasis type (艾灸联合拔罐治疗血瘀气滞型腰椎间盘突出症临床疗效观察) - ZHANG Xi (张西); GENG Qingwen (耿庆文); ZHOU Dengfang (周登芳); TANG Ling (唐玲); DUAN Peihang (段培航) (中西医结合护理)
Objective To investigate the effect of moxibustion combined with cupping therapy in the treatment of lumbar disc herniation of Qi-stagnation and Blood-stasis type. Methods Totally 60 patients with lumbar disc herniation of Qi-stagnation and Blood-stasis type were randomly divided into the observation group and control group, with 30 cases in each group. All patients received routine care, and those in the observation group were given moxibustion combined with cupping therapy. The improvement of disease-related symptom integrals and intervention efficacy were measured. Results Patients in the observation group achieved higher scores of assessment on clinical manifestation, quality of daily life and lumbar function compared with those in the control group (P＜0. 05). The total response rate in the observation group was 96. 67%(29/30), higher than 70. 00%(21/30) in the control group (P＜0. 05) . Conclusion The moxibustion combined with cupping therapy is effective to relieve the disease-related symptom and improve the quality of life in patients with lumbar disc herniation of Qi-stagnation and Blood-stasis type. (目的 探讨艾灸联合拔罐治疗血瘀气滞型腰椎间盘突出症患者的效果。方法 60例血瘀气滞型腰椎间盘突出症患者随机分为观察组和对照组, 各30例。对照组给予常规干预, 观察组在对照组基础上开展艾灸联合拔罐干预。观察2组患者干预后中医症状改善情况, 评价治疗效果。结果 观察组临床表现、日常生活质量、腰部活动度评分均高于对照组, 差异有统计学意义(P＜0. 05)。观察组总有效率96. 67%(29/30), 高于对照组的70. 00%(21/30), 差异有统计学意义(P＜0. 05)。结论 对血瘀气滞型腰椎间盘突出症患者采用艾灸联合拔罐干预能有效改善其中医症状, 提高患者生活质量。)